2000
DOI: 10.1046/j.1365-2109.2000.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg production in the salmon louse [Lepeophtheirus salmonis (Krøyer)] in relation to origin and water temperature

Abstract: Egg strings of salmon lice, Lepeophtheirus salmonis (Krøyer 1837), collected from farmed and wild Atlantic salmon had similar length and number of eggs string−1. Egg production was investigated at water temperatures from 7.1 °C to 12.2 °C. A regression model indicated that at low temperatures egg strings were longer and had more eggs. Mean length of single eggs was significantly smaller and the percentage of non‐viable eggs in the strings was higher at 7.1 °C than at 12.2 °C. Adult females survived for up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 19 publications
6
93
0
Order By: Relevance
“…In Ireland, salmon lice from wild hosts had ca 1000 eggs brood -1 , and lice from farmed fish had ca 500 eggs brood -1 . Heuch et al (2000) found that egg strings collected from farm sites and wild salmon in different parts of Norway did not have this clear pattern, though the longest egg strings came from lice on wild fish. Following our cautionary approach, we have included the former numbers ) in the present model.…”
Section: Assumptionsmentioning
confidence: 97%
“…In Ireland, salmon lice from wild hosts had ca 1000 eggs brood -1 , and lice from farmed fish had ca 500 eggs brood -1 . Heuch et al (2000) found that egg strings collected from farm sites and wild salmon in different parts of Norway did not have this clear pattern, though the longest egg strings came from lice on wild fish. Following our cautionary approach, we have included the former numbers ) in the present model.…”
Section: Assumptionsmentioning
confidence: 97%
“…Once attached to a host, copepodids eventually develop into adults, and adult females potentially release 26 to 68 nauplii through the protruding egg sacs daily, which then are free to develop to the copepodid stage and to infect other hosts (Heuch et al 2000, á Norði et al 2016. The growth of a sea lice population has an exponential nature (Frazer et al 2012) and is generally modelled as such (Costello 2006, Krkošek et al 2010, Frazer et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Several dispersion models have been developed which assume that the planktonic stages of the sea lice drift freely with prevailing currents close to the surface (Amundrud & Murray 2009, Adams et al 2012, Salama et al 2013, with recent works including vertical positioning as a response to environmental cues (Johnsen et al , 2016. Sea temperature is widely accepted as a basic factor influencing the growth rate of sea lice populations, as the generation time decreases with increasing temperature (Tully 1992, Heuch et al 2000. However, the relationship between temperature and the sea lice abundance is not a simple relationship, and annual peaks and troughs in the abundance of mobile L. salmonis may appear delayed compared with maximum and minimum annual temperature (Jansen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to the subclass Copepoda and has 8 developmental stages: 2 naupliar stages which disperse by drift, an infective free-swimming copepodite stage, 2 attached chalimus stages, 2 preadult stages, and the mature and reproductive stage (Heuch et al 2000, Boxaspen 2006, Hamre et al 2013). The louse is motile on the host in the preadult and mature stages.…”
Section: Introductionmentioning
confidence: 99%